zfh2 controls progenitor cell activation and differentiation in the adult Drosophila intestinal absorptive lineage - Rojas Villa, Sebastian E. (PLoS Genet, 2019)
Many tissues rely on resident stem cell population to maintain homeostasis. The balance between cell proliferation and differentiation is critical to permit tissue regeneration and prevent dysplasia, particularly following tissue damage. Thus, understanding the cellular processes and genetic programs that coordinate these processes is essential. Here, we report that the conserved transcription factor zfh2 is specifically expressed in Drosophila adult intestinal stem cell and progenitors and is a critical regulator of cell differentiation in this lineage. We show that zfh2 expression is required and sufficient to drive the activation of enteroblasts, the non-proliferative progenitors of absorptive cells. This transition is characterized by the transient formation of thin membrane protrusions, morphological changes characteristic of migratory cells and compensatory stem cell proliferation. We found that zfh2 acts in parallel to insulin signaling and upstream of the TOR growth-promoting pathway during early differentiation. Finally, maintaining zfh2 expression in late enteroblasts blocks terminal differentiation and leads to the formation of highly dysplastic lesions, defining a new late cell differentiation transition. Together, our study greatly improves our understanding of the cascade of cellular changes and regulatory steps that control differentiation in the adult fly midgut and identifies zfh2 as a major player in these processes.